Personal Hygiene and Soil-Transmitted Helminth Infection Among School Children in Karuwisi Health Centre Area, Makassar - Afandi, Naila Amalia; Fattah, Nurfachanti; Rasfayanah, Rasfayanah; Darussalam, Andi Husni Esa; Aisyah, Windy Nurul (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Soil-Transmitted Helminths (STH) infection remains a major public health concern among Indonesian school-aged children, largely influenced by personal hygiene behaviors. Objective: To analyze the relationship between personal hygiene practices and STH infection among elementary school children in the Karuwisi Health Centre area, Makassar. Methods: This analytical cross-sectional study involved 50 children, using the Kato-Katz method for stool examination and a structured questionnaire to assess hygiene behaviors; data were analyzed using Chi-square and Fisher’s exact tests. Results: The prevalence of STH infection was 24% (12/50), with all cases identified as Ascaris lumbricoides of light intensity. Poor handwashing behavior showed a strong association with STH infection (p < 0.001), and inadequate nail hygiene was also significantly related (p = 0.016). Conversely, the habit of not wearing footwear was not significantly associated with infection (p = 0.325). The findings indicate that transmission occurred primarily via the fecal-oral route rather than skin penetration. These results highlight that improving handwashing and nail hygiene behaviors can substantially reduce infection risk. Conclusion: Handwashing and nail cleanliness are key behavioral determinants of STH infection, emphasizing the need for school-based health education focusing on these preventive practices to mitigate STH transmission among children.